The Sovereignty of the Air Space and Its Protection in the Perspective of International Law: Some Aliens Intervention in Southeast Asian Countries - Siraji, Hafizh (Universitas Negeri Semarang, 2022)
State sovereignty in international law is not a solution, in the international world as a legal entity that acts as a subject of international law. This also happens between one country or another, which can then be announced the deeds agreed to by each country are not appropriate, because they must be approved by the deeds of other countries or we can call it the Relativity of State.There are three thoughts in understanding the concept of state sovereignty over developing air space. The first is that air space cannot be used or used by anyone because in principle, the state does not have sovereignty. Secondly, special rights such as freedom of air that do not limit the height of the airspace boundary are obtained by the State of the Netherlands. And finally, the principle that the state has freedom of airspace, but there is a territory or territorial zone that gives certain rights to the under the state that can be implemented. This research has the purpose of being able to know and analyze how the regulation and accountability of the state in an effort to protect and maintain the country's sovereignty over air space viewed from the perspective of international law. The research method used in this study is the normative juridical library method, where this normative juridical research is a study using literature with primary data such as laws and regulations, the scientific work of scholars, as well as from several books. Then it will be explained or described in a deductive description supported by literature study. Based on the results of research and discussion, we can find out that the thinking on the concept of state sovereignty territory starts from the three theoretical ideas mentioned earlier. Then put together in international agreements as stated in the 1944 Chicago International Civil Aviation Convention especially the definition of state sovereignty over air space, paragraph 1 which reads